1999
DOI: 10.1029/1999jc900114
|View full text |Cite
|
Sign up to set email alerts
|

Waves and currents over a fixed rippled bed: 3. Bottom and apparent roughness for spectral waves and currents

Abstract: Abstract. This paper is the third in a series of three that presents the results of experiments designed to verify the use of a single bottom roughness length scale for waves and currents over a rough bed. While the first two papers concentrated on the bottom roughnesses experienced by monochromatic wave and current boundary layer flows, this paper presents the results of additional experiments that investigate the use of an equivalent wave representation to extend these results to spectral wave and current bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Moreover, Madsen's [1994] relationship between friction factor and bed roughness is based on the assumption that k N is independent of ambient hydrodynamic conditions. This assumption has been validated for fixed beds in laboratory studies [Mathisen and Madsen, 1999 [Méndez and Losada, 2004;Méndez et al, 1999]. To reduce the impact of this effect on the present analysis, all instruments were placed inside the meadow, at least 100 m away from its leading and trailing edge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Madsen's [1994] relationship between friction factor and bed roughness is based on the assumption that k N is independent of ambient hydrodynamic conditions. This assumption has been validated for fixed beds in laboratory studies [Mathisen and Madsen, 1999 [Méndez and Losada, 2004;Méndez et al, 1999]. To reduce the impact of this effect on the present analysis, all instruments were placed inside the meadow, at least 100 m away from its leading and trailing edge.…”
Section: Discussionmentioning
confidence: 99%
“…While a current is likely to cause bending of the flexible vegetation leaves, it is not known in detail how the current affects sea grass. Additionally, experiments over fixed beds showed that k N is bed specific and is not affected by changing hydrodynamic conditions [Mathisen and Madsen, 1999]. Equation (18) should therefore yield a good first approximation, especially as values of C m are generally close to unity [Madsen, 1994].…”
Section: Wave Attenuationmentioning
confidence: 99%
“…Previous studies of bottom friction beneath random waves have been undertaken by Madsen [10][11][12][13][14][15][16][17][18][19] as well as Myrhaug and Holmedal [20][21][22]. Madsen [10] gave explicit wave friction factor formulas for spectral wave-current boundary layer flow.…”
Section: Introductionmentioning
confidence: 99%
“…Mathisen and Madsen [31][32][33] presented some results of the experimental investigation of the WBBL in the presence and in the absence of a constant current. It was shown that a sole scale of bottom irregularities can be used to characterize the state of the boundary layer and, moreover, that this scale remains invariable both in the presence and in the absence of a constant current.…”
mentioning
confidence: 98%
“…The results of laboratory and in-situ experiments carried out with an aim of investigation of the structure of nonstationary (fluctuating and wave) bottom boundary layers over smooth and rough bottoms are described in [15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Numerous works are devoted to the analysis of the conditions of development of turbulence and its characteristics in bottom boundary layers (see, e.g., [18,36]).…”
mentioning
confidence: 99%